Effect of Chitlac-nAg on Streptococcus mitis internalization into human gingival fibroblasts - Sancilio, Silvia; Valerio, Valentina; Rapino, Monica; Bosco, Domenico; Di Giulio, Mara; Travan, Andrea; Marsich, Eleonora; Cellini, Luigina; Cataldi, Amelia (Italian Journal of Anatomy and Embryology, 2015)
The surfaces of the oral cavity are always exposed to a broad variety of microor- ganisms able to form biofilms (Filoche et al, 2010) characterized by microbial com- munities that are organized as a network of cell-to-cell interactions. Streptococci are the predominant bacterial population of the oral environment and S.mitis in particular is the first colonizer of the oral biofilm (Di Giulio et al, 2013). Silver-based medical products have been proven to be effective in retarding and preventing bacterial growth. In order to prevent silver nanoparticles aggregation, a lactose-modified chitosan has been set up and resulted effective in stabilizing colloidal solution of nanoparticles (Chitlac-nAg) (Travan et al, 2009). Since many bacteria are able to internalize into eukaryotic cells, in our study we have investigated both the intracellular signaling governing S. mitis internalization into HGFs and the biological effect of ChitlacnAg on eukaryotic and prokaryotic cells in a co-culture model system. The internalization of S. mitis into HGFs is due to F-actin cytoskeleton reorganization and reduced expression within the cell. Immunofluorescence shows actin polymerization at invasion sites along with vinculin increased expression and spot organization. Vinculin is an adaptor protein that regulates the adhesion of integrin receptors to actin cytoskeleton. In presence of S. mitis an increment of integrin β1 and FAK expression, responsible for the entrance of the microorganism in HGFs is consistent, as revealed by electron microscopy analysis. This adhesion and uptake proteins profile is the same in the presence of saliva as well as bacteria uptake. When Chitlac-nAg is administred to cell culture the expression of all four proteins decreases and Ag nano- particles are recognized within the cells. Further, in presence of Ag nanoparticles the low amount of FAK is almost localized at nuclear level. In presence of Ag and S.mitis, the expression of all four proteins is increased, with respect to control, and F-actin cytoskeleton rearranged, while a raised number of bacteria is shown. This effect is mit- igated by the presence of saliva in cell culture, which probably prevents bacteria entry into the cell. These results let us hypothesize that Chitlac-nAg, developing its bacteri- cidal action could represent a good component of tooth paste and mouthwash.